Differential Equations SECOND ORDER (homogeneous) Graham S McDonald A Tutorial Module for learning to solve 2nd order (homogeneous) differential equations ● Table of contents ● Begin Tutorial c 2004 g.s.mcdonald@salford.ac.uk Table of contents 1. 2. 3. 4. 5. Theory Exercises Answers Solving quadratics Tips on using solutions Full worked solutions Section 1: Theory 3 1. Theory In this Tutorial, we will practise solving equations of the form: d2 y dy +b + cy = 0. dx2 dx i.e. second order (the highest derivative is of second order), linear (y and/or its derivatives are to degree one) with constant coefficients (a, b and c are constants that may be zero). a There are no terms that are constants and no terms that are only a function of x. If such terms were present, it would be conventional to collect them together on the right-hand-side of the equation. Here, we simply have a zero on the right-hand-side of the equals sign and this type of ordinary differential equation (o.d.e.) is called “homogeneous”. Since the o.d.e. is second order, we expect the general solution to have two arbitrary constants (these will be denoted A and B). Toc JJ II J I Back Section 1: Theory 4 A trial solution of the form y = Aemx yields an “auxiliary equation”: am2 + bm + c = 0, that will have two roots (m1 and m2 ). The general solution y of the o.d.e. is then constructed from the possible forms (y1 and y2 ) of the trial solution. The auxiliary equation may have: i) real different roots, m1 and m2 → y = y1 + y2 = Aem1 x + Bem2 x or ii) real equal roots, m1 = m2 → y = y1 + xy2 = (A + Bx)em1 x or iii) complex roots, p ± iq → y = y1 + y2 ≡ epx (A cos qx + B sin qx) Toc JJ II J I Back Section 2: Exercises 5 2. Exercises Find the general solution of the following equations. Where boundary conditions are also given, derive the appropriate particular solution too. Click on Exercise links for full worked solutions (there are 16 exercises in total). i h d2 y dy y 0 = dx Notation: y 00 = dx 2, Exercise 1. 2y 00 + 3y 0 − 2y = 0 Exercise 2. y 00 − 2y 0 + 2y = 0 Exercise 3. y 00 − 2y 0 + y = 0 ● Theory ● Answers ● Solving quadratics ● Tips Toc JJ II J I Back Section 2: Exercises 6 Exercise 4. y 00 = −4y Exercise 5. y 00 = 4y Exercise 6. 36y 00 − 36y 0 + 13y = 0 Exercise 7. 3y 00 + 2y 0 = 0 Exercise 8. 16y 00 − 8y 0 + y = 0 Exercise 9. y 00 + 4y 0 + 5y = 0 ; y(0) = 0 and y 0 (0) = 2 Exercise 10. y 00 + 6y 0 + 13y = 0 ; y(0) = 2 and y 0 (0) = 1 Exercise 11. y 00 + 6y 0 + 9y = 0 ; y(0) = 1 and y 0 (0) = 2 ● Theory ● Answers ● Solving quadratics ● Tips Toc JJ II J I Back Section 2: Exercises 7 Exercise 12. d2 y dy + +y =0 dx2 dx Exercise 13. d2 y dy −6 + 9y = 0 2 dτ dτ Exercise 14. d2 y dy +7 + 12y = 0 2 dτ dτ Exercise 15. d2 x dx +5 + 6x = 0 2 dτ dτ Exercise 16. 4 d2 x dx +8 + 3x = 0 2 dτ dτ ● Theory ● Answers ● Solving quadratics ● Tips Toc JJ II J I Back Section 3: Answers 8 3. Answers 1 1. y = Ae 2 x + Be−2x , 2. y = ex (A cos x + B sin x) , 3. y = (A + Bx)ex , 4. y = A cos 2x + B sin 2x , 5. y = Ae2x + Be−2x , 1 6. y = e 2 x (A cos x3 + B sin x2 ) , 2 7. y = A + Be− 3 x , 1 8. y = (A + Bx)e 4 x , Toc JJ II J I Back Section 3: Answers 9 9. y = e−2x (A cos x + B sin x); y = 2e−2x sin x , 10. y = e−3x (A cos 2x + B sin 2x); 11. y = (A + Bx)e−3x ; 1 12. y = e− 2 x (A cos y = (1 + 5x)e−3x , √ 3x 2 y = 12 e−3x (4 cos 2x + 7 sin 2x) , √ + B sin 3 2 x) , 13. y = (A + Bτ )e3τ , 14. y = Ae−4τ + Be−3τ , 15. x = Ae−2τ + Be−3τ , 3 1 16. x = Ae− 2 τ + Be− 2 τ . Toc JJ II J I Back Section 4: Solving quadratics 10 4. Solving quadratics To solve the quadratic equation: am2 + bm + c = 0, where a, b, c are constants, one can sometimes identify simple linear factors that multiply together to give the left-hand-side of the equation. Alternatively, one can always use the quadratic formula: m1,2 = −b ± √ b2 − 4ac , 2a to find the values of m (denoted m1 and m2 ) that satisfy the quadratic equation. Toc JJ II J I Back Section 5: Tips on using solutions 11 5. Tips on using solutions ● When looking at the THEORY, ANSWERS, SOLVING QUADRATICS or TIPS pages, use the Back button (at the bottom of the page) to return to the exercises ● Use the solutions intelligently. For example, they can help you get started on an exercise, or they can allow you to check whether your intermediate results are correct ● Try to make less use of the full solutions as you work your way through the Tutorial Toc JJ II J I Back Solutions to exercises 12 Full worked solutions Exercise 1. 2y 00 + 3y 0 − 2y = 0 Set y = Aemx → i.e. 2m2 y + 3my − 2y = 0 i.e. 2m2 + 3m − 2 = 0 : i.e. (2m − 1)(m + 2) = 0 i.e. m1 = i.e. 1 2 y1 = Ae dy = mAemx = my dx d2 y = m2 Aemx = m2 y dx2 Auxiliary Equation (A.E.) and m2 = −2 : 1 2x −2x and y2 = Be Two Different Real Roots : Two Independent Solutions 1 General solution is y = y1 + y2 = Ae 2 x + Be−2x , (A, B are arbitrary constants). Return to Exercise 1 Toc JJ II J I Back Solutions to exercises 13 Exercise 2. y 00 − 2y 0 + 2y = 0 Set y = Aemx , dy d2 y = my, = m2 y dx dx2 → m2 − 2m + 2 = 0 Auxiliary Equation (A.E.) i.e. am2 + bm + c = 0 with solutions m = 1 2a −b ± √ Since b2 − 4ac = (−2)2 − 4 · 1 · 2 = 4 − 8 = −4 < 0 , In fact, expect Complex (Conjugate) Solutions. √ √ m = 21 2 ± −4 = 12 2 ± 2 −1 = 1 ± i . For m = p ± iq , i.e. Toc b2 − 4ac . y = epx (A cos qx + B sin qx) y = ex (A cos x + B sin x), JJ II J since p = 1 and q = 1 . Return to Exercise 2 I Back Solutions to exercises 14 Exercise 3. y 00 − 2y 0 + y = 0 i.e. m2 − 2m + 1 = 0 (A.E.) (m − 1)2 = 0 i.e. m = 1 (twice) i.e. EQUAL REAL ROOTS Multiply one solution by x, to get two independent solutions i.e. y = y1 + xy2 = Aex + xBex = (A + Bx)ex . Return to Exercise 3 Toc JJ II J I Back Solutions to exercises 15 Exercise 4. y 00 = −4y √ √ m2 = −4 i.e. m= (A.E.) i.e. complex conjugate solutions of form p ± iq with p = 0, q = 2 . General solution, −1 · 4 = i · (±2) = ±2i y = epx (A cos qx + B sin qx) i.e. y = e0 (A cos 2x + B sin 2x) i.e. y = A cos 2x + B sin 2x . Return to Exercise 4 Toc JJ II J I Back Solutions to exercises 16 Exercise 5. y 00 = 4y A.E. is m2 = 4 i.e. m = ±2 i.e. real different roots ∴ y = y1 + y2 = Ae2x + Be−2x . Return to Exercise 5 Toc JJ II J I Back Solutions to exercises 17 Exercise 6. 3y 00 − 36y 0 + 13y = 0 A.E. is i.e. i.e. ∴ 36m2 − 36m + 13 = 0 p 1 m = 2·36 36 ± (−36)2 − 4 · 36 · 13 = 1 2 = 1 2 ± 1± 1 2 q 1− q −16 36 ± 13 i 1 y = e 2 x A cos m= 4·13 36 = 1 2 ± i 2 4 6 · 1 2 1 3x + B sin 1 3x . Return to Exercise 6 Toc JJ II J I Back Solutions to exercises 18 Exercise 7. 3y 00 + 2y 0 = 0 A.E. is 3m2 + 2m = 0 Real different roots : i.e. i.e. m(3m + 2) = 0 i.e. m1 = 0 and m2 = − 23 2 y = Ae0·x + Be− 3 x 2 y = A + Be− 3 x . Return to Exercise 7 Toc JJ II J I Back Solutions to exercises 19 Exercise 8. 16y 00 − 8y 0 + y = 0 A.E. is 16m2 − 8m + 1 = 0 Real equal roots: Toc i.e. (4m − 1)2 = 0 i.e. m= 1 4 (twice) 1 y = (A + Bx)e 4 x . JJ II J Return to Exercise 8 I Back Solutions to exercises 20 Exercise 9. y 00 + 4y 0 + 5y = 0 ; y(0) = 0 A.E. m2 + 4m + 5 = 0, m= 1 2 −4 ± √ y 0 (0) = 2 and 16 − 20 = −2 ± 22 i = −2 ± i y = e−2x (A cos x + B sin x) . General solution is Particular solution has y = 0 when x = 0 i.e. 0 = e0 (A cos(0) + B sin(0)) = 1 · (A + 0) = A Toc i.e. A=0. And dy dx JJ II = 2 when x = 0 J I Back Solutions to exercises A = 0 gives 21 y = e−2x B sin x dy dx = −2e−2x B sin x + e−2x B cos x = Be−2x (cos x − 2 sin x) i.e. 2 = B · e0 [cos(0) − 2 sin(0)] = B · 1[1 − 0] i.e. B =2. ∴ particular solution is y = 2e−2x sin x . Return to Exercise 9 Toc JJ II J I Back Solutions to exercises 22 Exercise 10. y 00 + 6y 0 + 13y = 0 ; y(0) = 2 A.E. m2 + 6m + 13 = 0 Toc y 0 (0) = 1 √ −6 ± 36 − 52 √ = −3 ± 12 −16 1 2 i.e. m= i.e. m = −3 ± 2i y = e−3x (A cos 2x + B sin 2x) . General solution is Particular solution and has y = 2 when x = 0 i.e. 2 = e0 (A cos(0) + B sin(0)) i.e. A=2. JJ II J I Back Solutions to exercises dy dx 23 = −3e−3x (A cos 2x + B sin 2x) + e−3x (−2A sin 2x + 2B cos 2x) = e−3x [(2B − 3A) cos 2x − (3B + 2A) sin 2x] 1 = e0 [(2B − 3A) cos(0) − (3B + 2A) sin(0)] i.e. i.e. i.e. i.e. ∴ dy dx = 1 when x = 0 1 = 2B − 3A 1 = 2B − 6 (using A = 2) 7 2 = B. Particular solution is y = 12 e−3x (4 cos 2x + 7 sin 2x) . Return to Exercise 10 Toc JJ II J I Back Solutions to exercises 24 Exercise 11. y 00 + 6y 0 + 9y = 0 ; y(0) = 1 A.E. is m2 + 6m + 9 = 0 i.e. (m + 3)2 = 0 i.e. m = −3 (twice) General solution : y = (A + Bx)e−3x . Particular solution has y = 1 when x = 0 i.e. 1 = (A + 0)e0 i.e. A=1. Toc JJ y 0 (0) = 2 and II J I Back Solutions to exercises dy dx 25 = Be−3x + (A + Bx) · (−3)e−3x = e−3x [B − 3(A + Bx)] i.e. 2 = e0 [B − 3(A + 0)], i.e. 2 = B − 3A i.e. B=5 ∴ since dy dx = 2 when x = 0 (using A = 1) . Particular solution is y = (1 + 5x)e−3x . Return to Exercise 11 Toc JJ II J I Back Solutions to exercises Exercise 12. d2 y dx2 26 + dy dx +y =0 Set y = Aemx , A.E. i.e. dy = my , dx m2 + m + 1 = 0 √ m = 12 [−1 ± 1 − 4] = − 12 ± d2 y = m2 y dx2 √ 3 2 i i.e. p ± iq with p = − 12 √ q= General solution: i.e. px 3 2 y = e (A cos qx + B sin qx) √ √ x y = e− 2 A cos 23x + B sin 23x . Return to Exercise 12 Toc JJ II J I Back Solutions to exercises Exercise 13. d2 y dτ 2 27 dy − 6 dτ + 9y = 0 A.E. m2 − 6m + 9 = 0 i.e. (m − 3)2 = 0 i.e. m=3 and y = Ae3τ (twice) (twice) To get two independent solutions, multiply one by τ i.e. y = (A + Bτ )e3τ . Toc JJ Return to Exercise 13 II J I Back Solutions to exercises Exercise 14. d2 y dτ 2 28 dy + 7 dτ + 12y = 0 A.E. m2 + 7m + 12 = 0 i.e. (m + 4)(m + 3) = 0 i.e. m1 = −4 and m2 = −3 i.e. two different real roots giving two independent solutions i.e. y1 = Ae−4τ and y2 = Be−3τ general solution is y = y1 + y2 = Ae−4τ + Be−3τ . Return to Exercise 14 Toc JJ II J I Back Solutions to exercises Exercise 15. d2 x dτ 2 29 + 5 dx dτ + 6x = 0 Set x = Aemτ , i.e. A.E. m2 + 5m + 6 = 0 i.e. (m + 2)(m + 3) = 0 i.e. m1 = −2 and dx = mx, dτ m2 = −3 and d2 x = m2 x dτ 2 (two different real roots) These give two independent solutions x(τ ) i.e. x1 = Ae−2τ general solution is x(τ ) = Ae−2τ + Be−3τ . and x2 = Be−3τ Return to Exercise 15 Toc JJ II J I Back Solutions to exercises 30 2 Exercise 16. 4 ddτx2 + 8 dx dτ + 3x = 0 A.E. 4m2 + 8m + 3 = 0 i.e. (2m + 3)(2m + 1) = 0 i.e. m1 = − 32 i.e. and m2 = − 12 − 32 τ x1 (τ ) = Ae (different real roots) 1 and x2 (τ ) = Be− 2 τ 3 (independent solutions) 1 ∴ general solution is x(τ ) = Ae− 2 τ + Be− 2 τ . Return to Exercise 16 Toc JJ II J I Back